Effect of Low Pressure and Low Oxygen Treatments on Fruit Quality and the In Vivo Growth of Penicillium digitatum and Penicillium italicum in Oranges - Archer, John; Pristijono, Penta; Vuong, Quan V.; Palou, Lluís; Golding, John (MDPI, 2022)
Penicillium digitatum and P. italicum are the major postharvest pathogens in citrus. To reduce postharvest decay, the use of low-oxygen (0.9 kPa O2) (LO) or low-pressure (6.6 kPa) (LP) treatments were evaluated during the storage of navel oranges for four or eight days. The results showed that exposure to both LO and LP treatments reduced in vivo pathogen growth compared to the untreated (UTC) oranges, with LO being the most effective. The effects of LO and LP on fruit metabolism and quality were further assessed, and it was found that there was no effect on fruit ethylene production, respiration rate, TSS (total soluble solids), TA (titratable acidity) or fruit firmness. However, both LO and LP treatments did have an effect on juice ethanol concentration and fruit weight-loss. The effect of adding exogenous ethylene at either LP (1 µL/L) or atmospheric pressure (AP) (at either 0.1, 1 µL/L) was also evaluated, and results showed that the addition of ethylene at these concentrations had no effect on mould diameter at LP or AP. Therefore, both LO of 0.9 kPa O2 and LP of 6.6 kPa at 20 °C are potential non-chemical postharvest treatments to reduce mould development during storage with minimal effects on fruit quality.